2018
DOI: 10.1186/s12992-018-0372-7
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic risk factors for early childhood underweight in Bangladesh

Abstract: BackgroundUnderweight is a major cause of global disease burden. It is associated with child mortality and morbidity, and its adverse impact on human performance and child survival is well recognized. Underweight is a major public health problem in Bangladesh, which is amongst the highest underweight prevalent countries in the world. The objectives of our study were to determine the national and regional prevalence rates of underweight and severe underweight in Bangladesh, and to investigate the association of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 53 publications
6
50
0
Order By: Relevance
“…Besides, there is a general consensus that higher education leads to higher income. Hence, increasing household earnings enables parents to invest more on health care services and proper food intake for their children ( Chowdhury et al., 2018 ) might be the reason of lower stunting rate of educated parents.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, there is a general consensus that higher education leads to higher income. Hence, increasing household earnings enables parents to invest more on health care services and proper food intake for their children ( Chowdhury et al., 2018 ) might be the reason of lower stunting rate of educated parents.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have identified different socioeconomic and maternal factors that are strongly associated with different forms of undernutrition (ie, stunting, wasting, and underweight). [5][6][7][8]28,29 Based on the published literature, a number of explanatory variables, such as age and sex of the children, maternal age, education, access to electronic media, residence, and socioeconomic status, were included in the decomposition analysis. Maternal education was categorized as no education, primary level of education, and secondary and higher secondary level of education.…”
Section: Major Explanatory Variablesmentioning
confidence: 99%
“…Also, they have consumed family food, and contamination is more likely to occur in food, especially in rural areas since sanitation is bad. 15,17 The result of this study shows a significant relationship between the total number of toddlers in households with underweight in rural areas, but it is not significantly related to the urban areas. This result shows families with more than 1 child in a rural area have a risk of toddlers being underweight by 1.24 times compared to families who only have 1 toddler.…”
Section: Methodsmentioning
confidence: 65%